The Combined Effect of Mechanical and Chemical Stimulation on the Differentiation of Induced Pluripotent Stem Cells into Cardiomyocytes. - Lau, Jason Joseph. (Tufts Archival Research Center, 2005)
We modified an established procedure used to chemically differentiate induced pluripotent stem cells into cardiomyocytes by incorporating mechanical stimulation and we assessed the early effects of combined stimulation. We designed the Arbitrary Waveform Membrane Stretcher (AWMS) which can stretch the membranes of a Flexcell plate with any waveform including physiologically relevant cardiac waveforms. The AWMS was designed to address limitations of vacuum-based cell stretchers through the use of pulse width modulation control of a moving magnet linear actuator to produce arbitrary waveforms, a feedback system to adjust for changing compliance of Flexcell membranes, and independent control of each plate for multiple simultaneous experiments. To mechanically stimulate cells, we optimized a method to transfer undifferentiated iPS cells to Flexcell plates and modified an existing process that is known to efficiently differentiate iPS cells through growth factor exposure. We observed varied expression of cardiac markers in the combined stimulation cell populations compared to chemical induction alone.